BRIDGING THE COMPLIANCE GAP: ISLAMIC MARKETING COMPLIANCE IN MINDANAO’S HALAL FOOD SECTOR - Maria Stella G. Codas (International Journal of Application on Economics and Business, 2025)
As Halal food gains global popularity, there is a growing need to understand how businesses put Islamic marketing principles into practice, especially in areas with smaller Muslim populations. This study explores the extent to which Halal restaurants in selected areas of Mindanao, Philippines, practice Islamic Marketing (IM) based on the 4Ps framework: Product, Price, Place, and Promotion. Using a descriptive survey design, data were gathered from 68 owners, managers, and supervisors of Halal-certified restaurants. Results show that the overall implementation of Islamic Marketing practices was at a “Moderate Extent” (Weighted Mean = 3.1). Among the four dimensions, Product received the highest rating, highlighting strong attention to Halal authenticity and quality, while Promotion and Place ranked lowest, pointing to challenges in visibility and distribution. The study also found a significant relationship between respondents’ profiles—such as age, educational attainment, years in service, and position—and their assessment of IM practices, suggesting that management awareness and experience influence the level of compliance. These findings reveal a gap between policy and practical implementation and align with other studies reporting similar issues in pricing and promotion strategies. To strengthen Halal marketing compliance, the study recommends capacity-building programs, such as seminars and awareness campaigns, aimed at improving understanding of Islamic business principles and building stronger consumer trust within Mindanao’s Halal food sector.